MODELLING OF MOTION OF BODIES NEAR TRIANGULAR LAGRANGIAN POINTS - Bobrov, O. A. (Одеські астрономічні публікації, 2014)
In this paper, we consider a system of three bodies connected by gravity, two of which are of comparable mass (the Sun and Jupiter), and the third is negligible and it is located in one of the triangular Lagrange points (restricted 3 – body problem). We used the equations of motion in a planar coordinate system that rotates together with massive bodies. Several programs have been written in the programming environment Pascal ABC, in order to build the trajectory of a small body, to indicate the osculating orbit around a massive body, to display equipotential surfaces